Evaluation of phosphatidylserine-dependent antiprothrombin antibody testing for the diagnosis of antiphospholipid syndrome: results of an international multicentre study. (March 2017) - Amengual, O; Forastiero, R; Sugiura-Ogasawara, M; Otomo, K; Oku, K; Favas, C; Delgado Alves, J; Žigon, P; Ambrožič, A; Tomšič, M; Ruiz-Arruza, I; Ruiz-Irastorza, G; et al.
Objective: A task force of scientists at the International Congress on Antiphospholipid Antibodies recognized that phosphatidylserine-dependent antiprothrombin antibodies (aPS/PT) might contribute to a better identification of antiphospholipid syndrome (APS). Accordingly, initial and replication retrospective, cross-sectional multicentre studies were conducted to ascertain the value of aPS/PT for APS diagnosis. Methods: In the initial study (eight centres, seven countries), clinical/laboratory data were retrospectively collected. Serum/plasma samples were tested for IgG aPS/PT at Inova Diagnostics (Inova) using two ELISA kits. A replication study (five centres, five countries) was carried out afterwards. Results: In the initial study ( n  = 247), a moderate agreement between the IgG aPS/PT Inova and MBL ELISA kits was observed ( k  = 0.598). IgG aPS/PT were more prevalent in APS patients (51%) than in those without (9%), OR 10.8, 95% CI (4.0–29.3), p  < 0.0001. Sensitivity, specificity, positive (LR+) and negative (LR–) likelihood ratio of IgG aPS/PT for APS diagnosis were 51%, 91%, 5.9 and 0.5, respectively. In the replication study ( n  = 214), a moderate/substantial agreement between the IgG aPS/PT results obtained with both ELISA kits was observed ( k  = 0.630). IgG aPS/PT were more prevalent in APS patients (47%) than in those without (12%), OR 6.4, 95% CI (2.6–16), p  < 0.0001. Sensitivity, specificity, LR + and LR– for APS diagnosis were 47%, 88%, 3.9 and 0.6, respectively. Conclusions: IgG aPS/PT detection is an easily performed laboratory parameter that might contribute to a better and more complete identification of patients with APS.